The socio-economic determinants of maternal health care utilization in Ghana - Abor, P.A.; Abekah-Nkrumah, G.; Sakyi, K.; Adjasi, C.K.D.; Abor, J. (International Journal of Social Economics, 2011)
Purpose: The study aims to examine the socio-economic determinants of maternal health services utilization in Ghana. Design/methodology/approach: Probit and ordered probit models are employed in this study. Findings: The results generally indicate that most women in Ghana undertake the required visits for antenatal services and also take both doses of the tetanus toxoid vaccine as required by World Health Organization. However, the results show low levels of usage in terms of the other maternal health care services (i.e. prenatal care, delivery at a health facility, and postnatal care). There is clearly an urgent need to develop innovative strategies that will help upscale intervention especially for improvement in the use of these services by women in Ghana. The regression results reveal that utilization of maternal health services and intensity of use of antenatal services are influenced by age of mother, type of birth, education of mother, ethnicity, economic status, geographic location, residence, and religious affiliation. Obviously, this suggests that more than medical factors are responsible for the differences in the use of maternal health services by women in Ghana as well as the decision on the number of visits to undertake with respect to antenatal visits. Originality/value: The findings of this study have important implications for health policy formulation targeted at improving maternal health care service utilization. © Emerald Group Publishing Limited.
Keywords: Care; Ghana; Health care; Maternal health; Maternity services; Socio-economic determinants; Socio-economic regions; Utilization